Ocular changes –cataract and retinal lesion- in Spontaneously Diabetic Torii (SDT) fatty rats, an obese type 2 diabetic model - Maekawa, Tatsuya; Nakamura, Sanae; Miyajima, Katsuhiro; Uno, Kinuko; Yamaguchi, Ayane; Mandai, Kouhei; Gotoh, Takayuki; Shinohara, Masami; Shinozaki, Yuichi; Sasase, Tomohiko; Fatchiyah, Fatchiyah; Ohta, Takeshi (JSMARTech, 2021)
Cataract and retinopathy remain the preventable cause of blindness worldwide, and many pharmacological strategies have been proposed for the treatment of these eye diseases. Animal models play an important role in understanding the pathophysiological features of eye disease and developing for a new therapy. In this study, we investigated the development of cataract and retinal lesion with diabetes using an obese type 2 diabetic models SDT fatty rat. Macroscopic analysis in eyes was performed from 16 to 24 weeks of age and histological analysis was performed at 24 weeks of age. As a result, the lens cloudiness was observed from 19 weeks of age and the degree of the cloudiness was more progressed until 24 weeks of age. Histopathological findings, such as degeneration of lens fiber and shortening and irregular arrangement of cone and rod in retinal tissue, were observed at 24 weeks of age. In conclusion, SDT fatty rats may be useful to understand the pathological features in diabetic cataract and retinopathy develop a new therapy for the disease.